Денежная масса и норма процента в равновесии экономики - Дунаев, Б.Б. (Кибернетика и системный анализ, 2010)
Зміна впродовж року суми наявних грошей та депозитів на вимогу приведе до пропорційної зміни грошового дефлятора, яка забезпечить постiйною реальну кількість грошей, і не вплине на швидкість їх обiгу. Швидкість обiгу грошей дорівнює відношенню реального сукупного попиту на блага до реальної кількості грошей. Норма відсотка пропорційна квадрату швидкості обiгу грошей, не впливає на кількість грошей в обігу впродовж року і на рівень цін і не може регулювати рівновагу економіки. Any change in the sum of the cash on hand and on demand deposits during a year causes the proportional change in the money deflator, which provides the invariability of the real amount of money in circulation and does not exert influence on the velocity of money circulation. The velocity of money circulation is equal to the ratio of the real composite demand for boons to the real amount of money in circulation. The interest rate is proportional to the square of velocity of circulation of money, does not exert influence on the amount of money in annual circulation and on the standard of prices, and cannot regulate the economic equilibrium.